2003
DOI: 10.1074/jbc.m303977200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Profiling with Epstein-Barr Nuclear Antigen-1 Reveals an Interaction with the Herpesvirus-associated Ubiquitin-specific Protease HAUSP/USP7

Abstract: The Epstein-Barr nuclear antigen-1 (EBNA1) protein of Epstein-Barr virus is important for the replication, segregation, and transcriptional activation of latent Epstein-Barr virus genomes; has been implicated in host cell immortalization; and avoids proteasomal processing and cell-surface presentation. To gain insight into how EBNA1 fulfills these functions, we have profiled cellular protein interactions with EBNA1 using EBNA1 affinity chromatography and tandem affinity purification (TAP) of EBNA1 complexes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
240
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(253 citation statements)
references
References 54 publications
11
240
2
Order By: Relevance
“…It is more likely to be a proofreading enzyme that regulates the stability of specific target proteins by antagonizing their polyubiquitination. Indeed, it has been shown that USP7 specifically deubiquitinates p53 in vitro and in vivo (34) and has a similar effect on the Epstein-Barr virus regulatory protein EBNA-1 (32). In that USP7 binds to both p53 and EBNA-1, it may be that its binding partners are protected from ubiquitination by USP7 activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is more likely to be a proofreading enzyme that regulates the stability of specific target proteins by antagonizing their polyubiquitination. Indeed, it has been shown that USP7 specifically deubiquitinates p53 in vitro and in vivo (34) and has a similar effect on the Epstein-Barr virus regulatory protein EBNA-1 (32). In that USP7 binds to both p53 and EBNA-1, it may be that its binding partners are protected from ubiquitination by USP7 activity.…”
Section: Discussionmentioning
confidence: 99%
“…1, D and E). Higher amounts of USP7 (on the order of 1 g in similar assays instead of the 5 ng used here) have, however, been shown to cleave a similar model isopeptidelinked substrate (32), and therefore the protein does not lack the potential for this activity.…”
Section: Enzymatic Activity Of Purified Usp7 On Model Substrates Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Resistance to proteolysis may be required for the capacity of EBNA-1 to act as a transcriptional regulator either alone or together with interacting cellular proteins. Indeed, using both affinity chromatography and TAP-tagging approaches, Holowaty et al (2003b) have recently shown that EBNA-1 interacts with the isopeptidase USP7, also known as herpesvirus-associated ubiquitin-specific protease, HAUSP. This nuclear enzyme was first identified by virtue of its interaction with the ICP0 protein of herpes simplex virus type 1, which is required for efficient initiation of the HSV-1 lytic cycle (Everett et al, 1997).…”
Section: The Rescue Program: Lmp-2a and The Capture Of Cellular Ubiqumentioning
confidence: 99%